Outcome of Patients Presenting with Peripartum Cardiomyopathy in a Tertiary Care Center of Nepal - Shakya, Smriti; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Manandhar, Bhawani; Khanal, Rajaram; Shrestha, Suraj; Sharma, Manju (Journal of Cardiology and Cardiovascular Medicine, 2024)
Purpose: Peripartum cardiomyopathy is a rare life-threatening cardiomyopathy of unknown etiology with significant maternal morbidity and mortality. It causes heart failure due to left ventricular systolic dysfunction with or without left ventricular dilatation in the last month of pregnancy up to 5 months postpartum in previously healthy women. We aimed to determine short-term outcomes of peripartum cardiomyopathy clinically as well as in terms of left ventricular systolic function and to study the clinical profile and associated risk factors. Patients and methods: A prospective observational study was carried out in the Department of Cardiology of Manmohan Cardiothoracic Vascular and Transplant Center, Institute of Medicine, Kathmandu, Nepal, from July 2018 to January 2022. All the patients with peripartum cardiomyopathy who presented to the department of cardiology were enrolled in the study and re-evaluated with echocardiography at 6 months. Results: A total of 68 women met the inclusion criteria. The mean age was 28.38 ± 5.5 years (range 19 to 44 years). The most common clinical presentation was dyspnea followed by lower limb edema. Six (8.8%) patients presented during the last month of pregnancy whereas 62 (91.2%) patients presented in the postpartum period. The mean left ventricular ejection fraction on presentation was 30.01 ± 8.54. A full recovery was observed among 60.29% at 6 months. The mortality rate was 4.41%. Conclusion: Timely diagnosis and management of peripartum cardiomyopathy with standard therapy for heart failure leads to better recovery of left ventricular systolic function.